2011
DOI: 10.1016/j.jvs.2010.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of the Carotid Duplex Consensus criteria in the diagnosis of carotid artery stenosis

Abstract: The consensus criteria can be accurately used for diagnosing ≥ 70% stenosis; however, the accuracy can be improved for detecting 50% to 69% stenosis if the ICA PSV is changed to 140 to < 230 cm/s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 15 publications
6
76
0
5
Order By: Relevance
“…Its diagnostic accuracy, if performed by experienced sonographers, has shown to be >90% when compared with angiography [1,2]. A significant number of previous studies have shown that transcranial Doppler examination can add important information to carotid duplex scanning [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Its diagnostic accuracy, if performed by experienced sonographers, has shown to be >90% when compared with angiography [1,2]. A significant number of previous studies have shown that transcranial Doppler examination can add important information to carotid duplex scanning [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Carotid stenosis ≥70% on ultrasound was established based on predefined criteria of ICA peak systolic velocity >230 cm/s, or ICA end-diastolic velocity >100 cm/s, or ICA/common carotid artery peak systolic velocity ratio >4.0. 13,14 Controls were patients without CAS or history of atherosclerotic vascular disease (stroke, myocardial infarction, and peripheral arterial disease).…”
Section: Case and Control Statusmentioning
confidence: 99%
“…Atualmente vários exames podem ser realizados para a avaliação da doença das artérias carótidas, como a arteriografia convencional, a angiografia por ressonância nuclear magnética (ARNM), a angiotomografia (CTA) e a USV 88 . Nas últimas três décadas, a USV tornou-se o método mais utilizado para a avaliação das artérias carótidas extracranianas 2,89 . Isso se justifica por tratar-se de um método não invasivo, que não utiliza radiação ou contraste, fornece informações anatômicas e hemodinâmicas, tem boa reprodutibilidade, portabilidade e custo inferior aos demais exames diagnósticos.…”
Section: Quantificação Das Estenoses Carotídeas Pela Ultrassonografiaunclassified
“…AbuRahma e cols. 2 observaram que a melhor correlação entre as medidas realizadas pela USV e a arteriografia (teste de Pearson) ocorreu quando se usou a medida da VPS (r = 0,81), seguida pela medida da VDF (r = 0,70), razão VPSACI / VPS ACC (r = 0,57) e razão VDF ACI / VDF ACC (r = 0,54). Em nosso meio, também foi observada uma correlação muito boa entre os valores da VPSACI, da razão VPSACI / VPS ACC e VDF ACI com os graus de estenose da ACI encontrados na arteriografia (r = 0,81; r = 0,81; r = 0,78; todos com p < 0,001) 104 .…”
Section: Local Da Medida Das Velocidadesunclassified